SOSIALISASI PEMBUATAN DAN PROMOSI PRODUK SENI KRIYA KHAS SULAWESI TENGGARA PADA MAHASISWA JURUSAN TRADISI LISAN FAKULTAS ILMU BUDAYA UNIVERSITAS HALU OLEO - Rahmat Sewa Suraya (Anoa : Jurnal Pengabdian Masyarakat Sosial, Politik, Budaya, Hukum, Ekonomi, 2022)
Community Service Program, in the form of dissemination of the manufacture and promotion of Southeast Sulawesi typical craft art products to students majoring in Oral Traditions, Faculty of Cultural Studies, Halu Oleo University to increase student understanding in making Southeast Sulawesi handicrafts and their promotion as part of tourism industry products as well support the Merdeka-Learning Curriculum of the Merdeka Campus. It is done bearing in mind that there is no practice or direct observation in courses related to tourism, such as tourism promotion management and the tourism industry. As a result, several students experienced difficulties in understanding and implementing the lecture material received, as seen from the quality of student assignments. The results of the activity showed quite a high student enthusiasm in direct observation of the stages of making and promoting Southeast Sulawesi handicrafts by the Southeast Sulawesi Regional National Craft Council, which generally consisted of three categories, namely silver, woven, and woven fabrics.